Optimization of the intervention model of tourism empowerment based on sociocultural aspects - Ahmad Taufik Maulana Ramadan, Aat Ruchiat Nugraha, Feliza Zubair, Susie Perbawasari, (Opción, 2019)
The purpose of this study was to find out and explain the role of the government in intervening in the development of social-cultural tourism based on policy intervention. This study used a qualitative descriptive method approach. The results showed that the Government intervention model in the new autonomous region was very effective in the form of a policy of determining an area to become a tourism and agro-tourism village. Conclusions show that the power of government policy intervention will have a significant impact on increasing the welfare and participation of the community in developing tourist destinations.